Analisis Berpikir Kritis Siswa Kelas 5 dalam Mata Pelajaran IPS di SD Negeri Pucung Kidul 03 - Rifky Pramudya; Nungky Mawardani; Amelia Oktaryani Zahra; Shovi Sariyatus Surur; Saripah Saripah; Ika Khoirun Nisa; Gigih Winandika (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2025)
Education is important for humans to gain prosperity and happiness in life, so it can be said that education is a person's basic need in order to become a real human being as a whole. In this day and age, students are not only required to be able to master technology and information to compete, students are required to think critically which is more developed in order to solve problems that will occur. This study aims to determine the extent to which students are able to think critically through social studies subjects. This research uses descriptive quantitative research methods or non-experimental methods. The results showed that grade 5 students at SD Negeri Pucung Kidul 03 had a critical thinking attitude in the very good category.